Predictive Value of Galectin-3 and Brachial-Ankle Pulse Wave Velocity for Coronary Artery Calcification in Coronary Arteriography Patients. (16th May 2022) - Tian, Lei; Ding, Fenghua; Zhang, Ruiyan
Abstract : Objectives . To study the predictive value for coronary artery calcification (CAC) of plasma galectin-3 and brachial-ankle pulse wave velocity (BaPWV) in coronary arteriography (CAG) patients. Methods . Patients who received coronary arteriography (CAG) examination were recruited. The level of plasma galectin-3 was measured by the enzyme-linked immunosorbent assay. The arterial stiffness was analyzed by BaPWV and ankle-brachial index (ABI) which were measured using a volume-plethysmographic device. Receiver operating characteristic (ROC) curve was used to analyze the prognostic value of galectin-3 or BaPWV for coronary artery calcification (CAC). Results . The level of galectin-3 and BaPWV was significantly higher in CAC patients compared with that in control (p < 0.01 ). The level of plasma galectin-3 was positively correlated with BaPWV ( r  = −0.296, p < 0.01 ) and negatively correlated with ABI ( r  = −0.296, p < 0.01 ). ROC curve analysis revealed that galectin-3 ≥5.90 ng/ml was the most powerful predictor for CAC with sensitivity of 85.5% and specificity of 83.5%. The area under the curve (AUC) was 0.916. When the level of BaPWV was more than 1909 m/s, the sensitivity and specificity were 61.8% and 69.6%, respectively, for predicting CAC. The AUC was 0.646. Conclusions . The level of plasma galectin-3 increases significantly in CAC patients compared to control, and its level is related to BaPWV and ABI. Galectin-3 and BaPWV can be used to predict CAC, and the diagnosis value (sensitivity and specificity) of galectin-3 for CAC is better than that of BaPWV.